RANCANG BANGUN SISTEM INFORMASI PELAYANAN DAN PENGELOLAAN TIKET MASUK WISATA - Cucu Komala, Angga Erlangga Aditina (Universitas Majalengka, 2021)
The development of technology now is grow so fast and is a very tool that is needed by companies or organizations to get faster information. This is information expected to help with processing and speed up the work in progress. Mercury Sayang Kaak Hill is a tourist place in the Tejamulya Village, Argapura district. This Hill is a tourist place has visitors who want to play, enjoy the atmosphere of the highlands with photo spots and coolness that is typical of this tour and want to enjoy the green natural atmosphere with the presence of trees, mountains and plantations. Researchers saw the problems that in the entrance ticket service, which at this time ticketing services was recorded manually. namely the doorman or the person who guards in terms of serving visitors to buy and make payments. The income management or stage reports on the stages of the mercury hill, unfortunately the have so far still used the system in the book and have not used a system specifically for management data. A computerized recording system is needed that can support activities and Presentation of information can be faster, precise and accurate.